PERTUNJUKAN MUSIK RATIB RABANA KEBO DI DESA POTO KECAMATAN MOYO HILIR KABUPATEN SUMBAWA - Rudy Suryady; Abdul Alimun Utama (STRETTO: Jurnal Penyajian, Pengkajian dan Penciptaan Musik, 2023)
The Ratib Rabana Kebo music performance in Poto Village, Moyo Hilir District, Sumbawa Regency, is a rich cultural heritage with historical value and local cultural significance. This research uses participatory observation, interviews and literature study methods to document historical, cultural aspects and the role of musicians and traditional stakeholders in this performance. This music has long historical roots, colors people's daily lives, and reflects deeply held cultural norms. This article discusses musical performances that have an impact on the existence and future challenges faced in maintaining the sustainability of this tradition. By understanding cultural values ??and the role of musicians in the local context, it is hoped that we can encourage efforts to preserve and develop Ratib Rabana Kebo musical performances as an inseparable part of the cultural identity of the Poto Village community.